The use of Constructivists’ Approach in Teacher Preparation; A case of Primary Teachers Colleges of South Eastern Uganda - Gusango, Emmanuel; Maani, John; Ssetumba, John (American Journal of Education and Practice, 2021)
Purpose: The purpose of this study was to explore the implementation of constructivists' principles in teacher preparation in colleges and to establish whether the constructivist approaches were being used to teach students. Methodology: This phenomenological study explored the lived experiences of tutors and students in light of constructivists informed teaching. It involved 3 PTCs and 15 participants who were purposively sampled. The methodology for this study was qualitative with a phenomenological research design where data was gathered using in-depth multiple interviews and observation. The data collection and analysis followed Moustakas (1994) procedure. Findings: Data analysis and results revealed that tutor"˜s continue to rely on traditional approaches in both instruction and supervision of school practice. Unique Contribution to Theory, Practice and Policy: This research study adds to the body of knowledge about ways in which constructivists' informed teaching supports teaching effectiveness and promotes students' learning amplifying the need for reflective practice in instruction. The study recommends establishing and setting up Reflective Practice Laboratories in PTCs for tutors and students induction on several constructivists' practices that include reflection, clinical supervision, use and integration of ICT and other interventions in a proper and professional setting.